Multiple idiopathic cervical root resorption: Case report of an unusual presentation. (5th November 2020) - Samara, Elpida; Kelly, Emily; Walker, Rosamunde; Borumandi, Farzad
Abstract: Idiopathic cervical root resorption (ICRR) is a rare condition involving the cemento‐enamel junction of the teeth. Multiple idiopathic cervical root resorption (MICRR) involves several teeth with an unknown prevalence and aetiology. The resorptive lesions are often detected on routine radiographs or during clinical examination. The defects are often painless, hence they are usually diagnosed late and in an advanced stage when diagnosed clinically. The restoration of MICRR can be demanding with subsequent loss of the teeth affected. In this report, we describe the case of a 16‐year‐old female with MICRR, the therapeutic challenges and clinical burden for this young patient over a period of approximately 5 years.